Listening to cougar - Bekoff, Marc, editor; Lowe, Cara Blessley, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2007)
This spellbinding tribute to "Puma concolor" honors the big cat's presence on the land and in our psyches. Essays describe chance meetings with cougars. Biologists describe aspects of cougar ecology. Conservationists relate the political history of America's greatest cat. Short stories and essays consider cougar's significance to people. A timely and thoughtful blend of natural history and evocation of a mysterious creature.
Introducing cougar / Cara Blessley Lowe -- In absentia / Ted Kerasote -- The growl / Steve Edwards -- Lion markers / J. Frank Dobie -- Border cat / Janay Brun -- A puma's journey / Linda Sweanor -- To cry for vision / Christina Kohlruss -- Closer / Gary Gildner -- Sanctuary / David C. Stoner -- Talking with a cougar / Julia B. Corbett -- The sacred cat: the role of the mountain lion in Navajo mythology and traditional lifeway / Steve Pavlik -- Lion story / Rick Bass -- South Dakota cougar / Deanna Dawn -- My bush soul, the mountain lion / Suzanne Duarte -- Lion heart / Cara Blessley Lowe -- A lion, a fox, and a funeral / Marc Bekoff -- Hunting at night / Joan Fox -- A short, unnatural history / Wendy Keefover-Ring -- The shifting light of shadows / BK Loren -- Drought / Barry Lopez -- Cougar country safety tips -- Deaths by cougar attack, 1890-present -- Cougars killed by humans, 1900-2000 -- Mapping values: cougars and the perspectives of human stakeholders.
Keywords: Puma -- Anecdotes